Dance - Grau, Andree (Stoddart Publishing Co. Ltd, 1998)
Describes different types of dance, shows movements and exercises associated with each style and discusses choreography, dance companies and careers.
Keywords: Dance; Juvenile Nonfiction; Performing Arts